Beyond the Light Reflex: Rethinking Pupillary Assessment as a Cornerstone of Neurological Monitoring in Critical Care - Shibu Sasidharan; Sunali Nanayakkara; Soumya Madhusudhan (Current Medical Issues)
Pupillary assessment remains one of the oldest and most fundamental components of neurological examination in critical care. Despite technological advancements in monitoring modalities, the simple act of checking pupils continues to provide invaluable information regarding neurological status, potential deterioration, and therapeutic response. This perspective examines the evolving role of pupillary assessment in modern intensive care units, highlighting its continued relevance, recent technological innovations, implementation challenges, and future directions. As critical care medicine advances, proper integration of both traditional pupillary examination techniques and automated pupillometry can enhance neurological monitoring paradigms, potentially improving patient outcomes through earlier detection of neurological deterioration and more precise therapeutic guidance.